PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS QR CODE UNTUK MENINGKATKAN KOSA KATA BAHASA ARAB DI PERGURUAN TINGGI - Muhammad Hayyu. M; Sitti Saenab; Sukmawati Sukmawati; Hebrianti Hebrianti (IAI DDI Mangkoso, 2023)
This research is motivated by the urgency of digital learning media innovation in the era of disruption to overcome the stagnation of Arabic vocabulary mastery among university students. The main issue examined is how the integration of Quick Response (QR) Code-based interactive media can optimize memory retention and student learning independence. The research method employed is library research with content analysis techniques on various reputable literatures and regulations related to digital education. The results of the study indicate that the use of QR Code as a bridge to access multimedia content is proven to significantly increase students' cognitive engagement compared to conventional methods. The conclusion of this study reinforces that QR Code-based media is highly relevant to be implemented as a practical solution for flexible vocabulary learning. It is recommended for higher education institutions to integrate this technology into the Arabic language curriculum to create a more humanistic and adaptive learning ecosystem.